An Examination of Business Social Responsibility (BSR) On the Local Environment: A Proposed Framework on the Relationship between BSR and Small and Medium Enterprises (SMEs) Performance - Gorondutse, Abdullahi Hassan (Information Management and Business Review, 2013)
Business social responsibility (BSR) is receiving an increasingly significant issue for economic agents all over the world, due to a new attention to all the aspects of firm’s activities and their relationships with stakeholders. However few studies have considered the influence of BSR and organizational performances. Even if any the finding reveals inconsistencies’. Hence a mediating mechanism is suggested. This paper aims to provide a propose framework that examine the relationship between BSR and SMEs performance with mediating effect of organizational culture. Based on literature review, this paper proposes four constructs which can be used to identify the implementation at firm level. The constructs are commitment, passiveness, organizational culture, and SMEs performance.